1997
DOI: 10.1177/002224299706100105
|View full text |Cite
|
Sign up to set email alerts
|

Enviropreneurial Marketing Strategy: The Emergence of Corporate Environmentalism as Market Strategy

Abstract: Environmental concerns have begun to reshape the landscape in which global organizations compete. The demands and influences of the environmental movement are evident in the dollar value size of the environmentally conscious marketplace. In addition, the growing regulatory concerns over the environmental impact of corporate practices have begun to influence corporate strategies. The authors discuss the concept of an enviropreneurial marketing strategy, which reflects the confluence of social performance goals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
355
1
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(384 citation statements)
references
References 69 publications
7
355
1
21
Order By: Relevance
“…In addition to the direct influence on EI, regulation is likely to have an indirect effect through environmental strategies. Some empirical studies have shown the important influence of regulation on environmental strategies (Menon & Menon, 1997;Saha & Darnton, 2005;Tutore, 2013). Some empirical studies have shown the important influence of regulation on environmental strategies (Menon & Menon, 1997;Saha & Darnton, 2005;Tutore, 2013).…”
Section: Direct Effects On Eimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the direct influence on EI, regulation is likely to have an indirect effect through environmental strategies. Some empirical studies have shown the important influence of regulation on environmental strategies (Menon & Menon, 1997;Saha & Darnton, 2005;Tutore, 2013). Some empirical studies have shown the important influence of regulation on environmental strategies (Menon & Menon, 1997;Saha & Darnton, 2005;Tutore, 2013).…”
Section: Direct Effects On Eimentioning
confidence: 99%
“…3 In her study on the drivers of environmental strategy in electric utilities, Tutore (2013) showed that legislation represented the first driver. Menon and Menon (1997) suggest that firms acting in highly regulated industries are more likely to develop environmental strategies to keep their competitive position. Saha and Darnton (2005) argue that environmental regulation shows that a major pressure for firms to adopt an environmental strategy.…”
Section: Direct Effects On Eimentioning
confidence: 99%
“…Such goods and services will not compromise the needs of future generations (Hansen and Schrader, 1997). Responsible consumers have an important role in achieving sustainability (Priewasser, 1999), and their purchasing decisions have clearly been influenced by increased environmental awareness (Drumwright, 1994;Menon and Menon, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…3 For recent overviews, see Bénabou and Tirole (2010), Heal (2005), Kitzmueller and Shimshack (2012), Margolis, Elfenbein, andWalsh (2009), Christensen et al (2017), and Chowdhry, Davies, and Waters (2019). For examinations of corporate social responsibility as a marketing strategy, see Du, Bhattacharya, and Sen ((2007), (2010)), Maignan and Ferrell (2004), Menon and Menon (1997), Sen and Bhattacharya (2001), and Torelli, Monga, and Kaikati (2011). 4 For exceptions, see Hirshleifer and Shumway's (2003) study of the role of sun exposure on market movements or Birru's (2018) study of risk-taking and anomaly predictability based on shifts in mood throughout the week.…”
mentioning
confidence: 99%